Neutrophil P-selectin-glycoprotein-ligand-1 binding to platelet P-selectin enhances metalloproteinase 2 secretion and platelet-neutrophil aggregation - Abou-Saleh, Haissam; Théorêt, Jean-François; Yacoub, Daniel; Merhi, Yahye (Thrombosis and Haemostasis, 2005)
Platelets and neutrophils constitute a high source of metalloproteinases (MMPs), and their interactions via P-selectin and Pselectin- glycoprotein-ligand-1 (PSGL-1) are involved in thrombosis, vascular remodelling, and restenosis. We investigated the impact of these interactions on platelet MMP-2 secretion and function in platelet and neutrophil aggregation. The secretion of MMP-2 from human platelets was significantly increased threefold after thrombin activation, and enhanced two-fold in the presence of neutrophils. Neutrophil supernatant had no effect on platelet MMP-2 secretion. While no MMP-2 was detected in the supernatant of neutrophils, a high amount of MMP-9 was released by neutrophils, and remained unchanged upon thrombin activation or in the presence of platelets. Platelet P-selectin, which increased significantly after activation, triggered platelet binding to neutrophils that was completely inhibited by P-selectin or PSGL-1 antagonists, and was reduced by 50% with a GPIIb/ IIIa antagonist. P-selectin or PSGL-1 antagonism abolished the enhanced secretion of platelet MMP-2 in the presence of neutrophils and reduced platelet-neutrophil aggregation. Platelet activation and binding to neutrophils enhance the secretion of platelet MMP-2 via an adhesive interaction between P-selectin and PSGL-1, which contribute to increase platelet-neutrophil aggregation.
Keywords: Platelets; leukocytes; cell adhesion molecules; metalloproteinases